2022
DOI: 10.1038/s41598-022-16754-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome and cell type-specific molecular pathways of human non-alcoholic steatohepatitis

Abstract: The aim of this study is to characterize cell type-specific transcriptional signatures in non-alcoholic steatohepatitis (NASH) to improve our understanding of the disease. We performed single-cell RNA sequencing on liver biopsies from 10 patients with NASH. We applied weighted gene co-expression network analysis and validated our findings using a publicly available RNA sequencing data set derived from 160 patients with non-alcoholic fatty liver disease (NAFLD) and 24 controls with normal liver histology. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
(46 reference statements)
0
21
1
Order By: Relevance
“…Our study also observed that hub gene HLA-DRA was higher expressed in both macrophages and dendritic cells (Figure 8C). Intriguingly, previous reports examining human NASH livers using single-cell RNA sequencing reported that M-Mac-1 included three genes, HLA-DRA, HLA-DQA2 and HLA-DQB2 (63), which was related to NAFLD loci (57,64,65). Further, recent study reported that cDC-related gene expression signatures in human livers were associated with NASH pathology (66).…”
Section: Discussionmentioning
confidence: 94%
“…Our study also observed that hub gene HLA-DRA was higher expressed in both macrophages and dendritic cells (Figure 8C). Intriguingly, previous reports examining human NASH livers using single-cell RNA sequencing reported that M-Mac-1 included three genes, HLA-DRA, HLA-DQA2 and HLA-DQB2 (63), which was related to NAFLD loci (57,64,65). Further, recent study reported that cDC-related gene expression signatures in human livers were associated with NASH pathology (66).…”
Section: Discussionmentioning
confidence: 94%
“…For example, liver-resident KCs have been shown to have complex macrophage polarization, and scRNA-seq analysis has demonstrated differences in macrophage activation in NASH. 29 Non-parenchymal cells from NASH mouse livers have been isolated and marked by Trem2, and single-cell data showed that these cells are monocytederived macrophages. 24,28 Other studies have shown that tumor-associated macrophage-like cells are induced in NASH livers and are linked to hepatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, activated hepatic stellate cells have been identified as contributing to fibrosis in NASH through collagen deposition, and the single-cell secretome gene analysis has shown that they secrete stellakines associated with chronic liver injury. 24,29 These studies provide a deeper understanding of NAFLD's cellular and molecular mechanisms and can be used to determine potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations